A Study Protocol: Engagement of Lived Experience Voices for Analysis of Transformative Evidence in Mental Health Policy & Legislation (ELEVATE-MH) - Kalo C. Sokoto; Tina W. Masai; Sisikelelwe S. Gwanya-Mdletye; Olindah Silaule; S’thembile Phindile Promise Jili; Selamawit A. Tessema; Mohhadiah Rafique; Ghonda Lepkeh; Action Amos; Kimberly Kariuki; Yiknashewa Solomon; Senait Ghebrehiwet; et al. (PLoS ONE, 2026)
Mental health conditions affect almost one in seven people globally. In response to the Convention on the Rights of Persons with Disabilities (CRPD), efforts to strengthen mental health systems have included increased funding, destigmatization of mental health, and the engagement of People with Lived Experience (PWLE) in decision making. Yet the extent to which PWLE are engaged in mental health policy development is not well characterized in the literature. To that end, this study seeks to understand the engagement of PWLE in mental health policy making in Africa and identify strategies for enhancing meaningful engagement of PWLE. The study described in this protocol will employ a qualitative multi-methods approach, utilizing the Policy Triangle Framework to analyze the policy making process, and International Association for Public Participation Spectrum to identify the extent of PWLE engagement. We will perform a scoping review of national mental health policies and legislation. We will interview 50 key informants including mental health policymakers, advocates, and researchers, and conduct focus group discussions with 120 PWLE. Qualitative data will be subject to content and thematic analysis. Country-specific analyses will be followed by a cross-country synthesis. Findings will inform context specific and strategies to enhance meaningful engagement of PWLE in mental health policy making. These will be disseminated through stakeholder workshops in each country, academic publications, conferences, PWLE-led knowledge translation activities, and policy briefs co-authored with community advocates.